ANALISIS KANDUNGAN BORAKS DAN Escherichia coli PADA JAJANAN BAKSO SAPI YANG DIPERDAGANGKAN DI KOTA BANJARBARU - Nur Rahmi; Danang Biyatmoko; Salamiah Salamiah; Jamzuri Hadie (EnviroScienteae, 2015)
This study aims to determine how the content of borax and Escherichia coli on meatballs snacks and the factors that affect the food security of meatballs snacks by using Easy Method of Borax Test and Method of Most Probable Number (MPN) for Escherichia coli bacteria contamination. This research was conducted in Banjarbaru on 5 villages, and sampling technique used is stratified sampling. The results of the study showed that from 32 samples taken from five village location, it was not identified any borax based on PERMENKES No. 033 of 2012, while for the examination of Escherichia coli, there are 14 samples of meatballs (43.75%) which were eligible, and 18 samples of meatballs (56.25%) which containEscherichia coli ranges from 3.6 to 62 CFU /g or not meeting the criteria of ISO 7388: 2009. The factor that might not trigger the addition of borax is that the traders have a good knowledge and attitude toward borax which regarded as a toxic substance and can be harmful to health. Factors that cause microbial contamination of Escherichia coli on meatballs snacks is the lack of food hygiene and sanitation in the food processing, cooked food storage, transport, serving, sanitation facilities, and personnel handlers compared with the good supply of foodstuffs and food ingredients storage.